Loss of myoepithelial calponin‐1 characterizes high‐risk ductal carcinoma in situ cases, which are further stratified by T cell composition. Issue 7 (5th March 2020) - Mitchell, Elizabeth; Jindal, Sonali; Chan, Tiffany; Narasimhan, Jayasri; Sivagnanam, Shamilene; Gray, Elliot; Chang, Young Hwan; Weinmann, Sheila; Schedin, Pepper
Abstract: A hallmark of ductal carcinoma in situ (DCIS) progression is a loss of the surrounding ductal myoepithelium. However, whether compromise in myoepithelial differentiation, rather than overt cellular loss, can be used to predict the risk of DCIS progression is unknown. Here we address this question utilizing pure and mixed DCIS cases (N = 30) as surrogates for DCIS at low and high risk for progression, respectively. We used multiplex immunohistochemical staining to evaluate the relationship between myoepithelial cell differentiation and lymphoid immune cell types associated with poor prognostic DCIS. Our results show that myoepithelial calponin‐1 discriminates between pure and mixed DCIS lesions better than histological subtype, presence of necrosis, or nuclear grade. Additionally, focal loss of myoepithelial cells associated with increased PD‐1+CD8+ T cells, which suggests a link between the myoepithelium and immune surveillance. To identify associations between calponin‐1 expression and immune response, we performed unsupervised hierarchical clustering of myoepithelial and immune cell biomarkers on 219 DCIS lesions from 30 cases. Notably, the majority of pure (low‐risk) DCIS lesions clustered in a high calponin‐1, T cell low group, whereas the majority of mixed (high‐risk) DCIS lesions clustered in a low calponin‐1, T cell high group, specifically with CD8+ and PD‐1+CD8+ T cells. However, a subset of pure DCIS lesions had a similar calponin‐1 and immune signature as the majority of mixed DCIS lesions, which have low calponin‐1 and T cell enrichment—raising the possibility that these pure DCIS lesions might be at a high risk for progression.